دور وظيفة البحث والتطوير في تحسين الخدمات المقدمة في المؤسسات العمومية دراسة حالة مؤسسة اتصالات الجزائر - مريم شطي; شيماء عزوزة (جامعة الوادي University Of Eloued, 2024)
" تهدف هذه الدراسة إلى كشف ومعرفة دور وظيفة البحث والتطوير في تحسين الخدمات المقدمة في المؤسسات العمومية بمختلف أشكالها إدارية، صناعية، تجارية، مهنية أو اقتصادية، وقد اخترنا مجمع اتصالات الجزائر بالعاصمة كنموذج للدراسة التطبيقية، باعتبارها احدى المؤسسات العمومية الاقتصادية التي تقدم خدمة جد مهمة للأفراد والمؤسسات والمجتمع ككل. وفي ظل حداثة وحدة البحث والتطوير في هذه المؤسسة فقد تم الحصول على المعلومات اللازمة بتصميم استبانة اشتملت على 25 فقرة وعرضها على عينة الدراسة. ثم تم جمع وتحليل البيانات واختبار الفرضيات باستخدام الحزمة الإحصائية للعلوم الاجتماعية Spss v21. وخلصت الدراسة بجانبيها النظري والتطبيقي إلى أن وظيفة البحث والتطوير لها علاقة وثيقة بتحسين جودة الخدمة حيث تمكن المؤسسات العمومية الاقتصادية من تحديد نقاط الضعف في خدماتها الحالية وتطوير حلول لتحسينها، وأيضا إدخال خدمات جديدة تلبي احتياجات السوق المتغيرة عبر التركيز على العميل وفهم احتياجاته وتوقعاته. وقد لعبت هذه الوحدة دورا بارزا رغم حداثتها في تطوير وتحسين الخدمات المقدمة من مؤسسة اتصالات الجزائر. " "This study aims to reveal and know the role of the research and development function in improving the services provided in public institutions in their various administrative, industrial, commercial, professional or economic forms. We have chosen the Algiers Telecom Complex in the capital as a model for the applied study, as it is one of the economic public institutions that provides a very important service to individuals. institutions and society as a whole. In light of the modernity of the research and development unit in this institution, the necessary information was obtained by designing a questionnaire that included 25 items and presenting it to the study sample. Then the data was collected and analyzed and the hypotheses were tested using the Statistical Package for the Social Sciences (SPSS v21). The study, in both its theoretical and applied aspects, concluded that the research and development function has a close relationship with improving the quality of service, as it enables public economic institutions to identify weak points in their current services and develop solutions to improve them, and also introduce new services that meet the changing needs of the market by focusing on the customer and understanding his needs and expectations. Despite its modernity, this unit played a prominent role in developing and improving the services provided by Algeria Telecom. "
مذكرة ماستر
Keywords: وظيفة البحث والتطوير، مؤسسات عمومية، خدمات عمومية، اتصالات الجزائر، تحسين الخدمات; research and development function; public institutions; public services; Algeria Telecom; improving services